PENDAMPINGAN PEMBUATAN PETA RAWAN KEBENCANAAN GUNUNG MERAPI DESA KLAKAH, SELO, BOYOLALI - Fatimah Fatimah; Ayu Candra Kurniati; Paramitha Tedja Trisnaning (Universitas Mataram, 2023)
Service to villages affected by disasters is part of the government's efforts and conscience in reducing the risk of loss of life and the risk of material loss. This service was carried out in Klakah, Selo, Boyolali which was the KRB III eruption of Mount Merapi. The village government is trying to create a map of geological disaster vulnerability and regional planning, namely from regional planning (PWK). This map was created from primary data and secondary data to provide an image and analysis of the vulnerability of Klakah village. The aim is to create a disaster vulnerability map on a village scale with a population of around 3000 people. Provide information on the vulnerability of the Klakah area from disasters that have occurred and the geological condition of the Klakah village area. The method for implementing community service is to conduct a focus group discussion with the relevant government, namely Klakah village officials. Collect data, both population and regional data. Conduct surveys or field observations by looking at natural conditions in terms of geography and geology. This discussion forum succeeded in collecting secondary data in the form of regional data and population data. Primary data collected were temporary gathering points and evacuation routes to the village office. Data on rivers, rice fields and roads. This secondary and primary data will later be processed with ArGIs. The results will be regional maps and geological maps. The combination of regional and geological for this service is in the form of a disaster map at the Klakah village scale by dividing it into three disaster vulnerability zones from very vulnerable, moderately vulnerable and vulnerable. The results of the classification resulted in an analysis of the vulnerability of the Klakah area to eruptions. It is hoped that the Klakah village government can bridge the understanding of evacuation maps. The public can use the map as a guide to mitigating the Merapi eruption disaster.